Machine learning in chemistry : the impact of artificial intelligence - Cartwright, Hugh M., 1948- (Royal Society of Chemistry, 2020)
This book provides practical examples of machine learning applied to science to help researchers make an informed choice about using the method in chemistry.
Keywords: Chemistry -- Data processing.; Machine learning.; elektronické knihy; electronic books